Audiovisual angle and voice incongruence do not affect audiovisual verbal short-term memory in virtual reality - Cosima A. Ermert; Manuj Yadav; Jonathan Ehret; Chinthusa Mohanathasan; Andrea Bönsch; Torsten W. Kuhlen; Sabine J. Schlittmeier; Janina Fels (PLoS ONE, 2025)
Virtual reality (VR) environments are frequently used in auditory and cognitive research to imitate real-life scenarios. The visual component in VR has the potential to affect how auditory information is processed, especially if incongruences between the visual and auditory information occur. This study investigated how audiovisual incongruence in VR implemented with a head-mounted display (HMD) affects verbal short-term memory compared to presentation of the same material over traditional computer monitors. Two experiments were conducted with both these display devices and two types of audiovisual incongruences: angle (Exp 1) and voice (Exp 2) incongruence. To quantify short-term memory, an audiovisual verbal serial recall (avVSR) task was developed where an embodied conversational agent (ECA) was animated to speak a digit sequence, which participants had to remember. The results showed no effect of the display devices on the proportion of correctly recalled digits overall, although subjective evaluations showed a higher sense of presence in the HMD condition. For the extreme conditions of angle incongruence in the computer monitor presentation, the proportion of correctly recalled digits increased marginally, presumably due to raised attention, but the effect size was negligible. Response times were not affected by incongruences in either display device across both experiments. These findings suggest that at least for the conditions studied here, the avVSR task is robust against angle and voice audiovisual incongruences in both HMD and computer monitor displays.